Kritik atas Penafsiran Abdul Moqsith Ghazali tentang Keselamatan Non-Muslim - Asep Setiawan (Universitas Darussalam Gontor, 2016)
This article discusses the interpretation of Abdul Moqsith Ghazali to al Baqarah [2]: 62 and al-Maidah [5]: 69, on the salvation of non-Muslim community according to religious pluralism. He used three methods of interpretation, which are tafsîr mauḍû’i, uṣûl al-fiqh, and hermeneutics. He said that the combination of them will produce a full understanding. Even so, the results are not as expected. Moqsith interprets the verses that seemed to support the idea of pluralism textually, until reject the interpretation of mufassirîn. He concludes that two verses above, do not explain about the obligation of Jews, Christians, and Shabiah in order to believe in Prophet Muhammad, but only explain about the obligation to believe in Allah and the Last Day, and do good deeds as defined in their holy books. Thus, according to him, the Qur’an does not only recognize religious teachings and people of other religions, however, they will be saved by God as far as they practice their religion. It is clear that the results of the interpretation of Moqsith very contradictory and not in accordance with interpretations of the Muslim scholars. Because of Moqsith’s weakness in method of interpretation, so create a partial understanding that the Qur’an legalizes religious pluralism. On the contrary, it is clear that the majority of mufassirûn did not argue that way.